Foot-and-Mouth Disease Virus 3C Protease Antagonizes Interferon Signaling and C142T Substitution Attenuates the FMD Virus - Ekanayaka, Pathum; Shin, Sung Ho; Weeratunga, Prasanna; Lee, Hyuncheol; Kim, Tae-Hwan; Chathuranga, Kiramage; Subasinghe, Ashan; Park, Jong-Hyeon; Lee, Jong-Soo (Frontiers in Microbiology, 2021)
3C protease (3Cpro), a chymotrypsin-like cysteine protease encoded by the foot-and-mouth disease virus (FMDV), plays an essential role in processing the FMDV P1 polyprotein into individual viral capsid proteins in FMDV replication. Previously, it has been shown that 3Cpro is involved in the blockage of the host type-I interferon (IFN) responses by FMDV. However, the underlying mechanisms are poorly understood. Here, we demonstrated that the protease activity of 3Cpro contributed to the degradation of RIG-I and MDA5, key cytosolic sensors of the type-I IFN signaling cascade in proteasome, lysosome and caspase-independent manner. And also, we examined the degradation ability on RIG-I and MDA5 of wild-type FMDV 3Cpro and FMDV 3Cpro C142T mutant which is known to significantly alter the enzymatic activity of 3Cpro. The results showed that the FMDV 3Cpro C142T mutant dramatically reduce the degradation of RIG-I and MDA5 due to weakened protease activity. Thus, the protease activity of FMDV 3Cpro governs its RIG-I and MDA5 degradation ability and subsequent negative regulation of the type-I IFN signaling. Importantly, FMD viruses harboring 3Cpro C142T mutant showed the moderate attenuation of FMDV in a pig model. In conclusion, our results indicate that a novel mechanism evolved by FMDV 3Cpro to counteract host type-I IFN responses and a rational approach to virus attenuation that could be utilized for future vaccine development.